Verbal and nonverbal communication during hammer throw training and competition - Rata, G.; Rata, B. C.; Rata, M.; Mares, G.; Melinte, M. (Science, Movement & Health, 2012)
This paper is an observational study conducted between February and March 2012, on 14 Romanian athletes (hammer throwers) and 12 Romanian coaches, regarding the importance and use of the verbal and nonverbal communication during training and competitions. The study tried to confirm two hypotheses. We used as a research method the inquiry, represented by a questionnaire with 6 questions, on which each coach had to choose one answer. The analyzed answers have emphasized aspects that show the opinion of hammer throw athletes and coaches regarding the verbal and nonverbal communication. Their opinions reveal us that in training, there are small differences in the way in which the communication between the hammer throwers and their coaches is done. The athletes communicate 52.14% nonverbally, through gestures and facial expressions, and 47.86% verbally, while the coaches communicate 50.83% nonverbally, and 49.17% verbally. During athletic competitions, the throwers and the coaches communicate more nonverbally, 66.43% and 75.83%, respectively, than verbally, 33.57% and 24.17%, respectively. Outside their athletic life, the throwers communicate verbally with their coach more by phone (76.43%) than by written messages (on the Internet, or phone) (23.57%), while the coaches verbally communicate with the athletes orally in proportion of 85.83%, and use written verbal communication in proportion of 14.17%. Fatigue, noise, and weather represent over 50% of the total perturbing factors for the athletes, while the coaches perceive the athlete's tension, nervousness that leads to bad performances, and the athlete's fatigue, as representing over 50% of the total perturbing factors. The communication process is perturbed "most times" by distance and position in proportion of 57.14% for athletes, and in proportion of 58.33% for coaches. The first hypothesis, stating that the hammer throwers use the verbal communication and the nonverbal communication in different proportions during training than during competitions, was confirmed, just as the second hypothesis, stating that the nonverbal communication is used more than the verbal communication by the hammer throwers and their coaches, during training and competitions, was also confirmed.